Analysis of Facilities and Infrastructure Management Government Sports Institutions - Iwan Setiawan; Boby Helmi; Ika Endah Puspita Sari; Riadi Saputra (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2022)
Sports activities require sports facilities and infrastructure in general. This study aims to examine the management of the procurement of sports facilities and infrastructure of the Department of Youth and Sports of Binjai City based on the management functions of Planning, Organizing, Actuating, and Controlling (POAC). This research is a type of qualitative descriptive research. The results showed that the application of management functions (1) Planning management in the procurement of sports facilities and infrastructure needs in Binjai City is carried out with proposals from the community and proposals from sports (2) Organizing management is the responsibility of the field of sports facilities and infrastructure and collaborates with stakeholders (3) Implementation management is carried out if the proposal from planning has been discussed and the budget has been determined (4) Supervision management is carried out by monitoring at every stage (5) The response of the Binjai community who felt the impact of the procurement of sports facilities and infrastructure in Binjai City got good results.